Effect of Exercise Training with Consideration of Potential Moderating Variables in Patients with Atrial Fibrillation: A Systematic Review and Meta-Analysis - Agustín Manresa-Rocamora; Laura Fuertes-Kenneally; Noemí Sempere-Ruiz; Carles Blasco-Peris; Alicia Ibáñez-Criado; Vicente Climent-Payá; José Manuel Sarabia (Sports Medicine - Open)
Abstract Background Exercise-based cardiac rehabilitation (CR) shows promise as an adjunctive treatment for patients with atrial fibrillation (AF). Previous evidence has highlighted its beneficial impact in this population. However, studies exhibit significant heterogeneity and often fail to differentiate between AF types. Furthermore, the specific influence of training variables such as exercise modality or intensity on the exercise-induced effects remains unclear. Therefore, the aim of our review was to assess the effect of exercise training (i.e., aerobic, resistance, and combined exercise), on exercise capacity, quality of life (QoL), resting heart rate (HR), AF burden, and symptoms in AF. Methods Electronic searches were conducted in PubMed, Embase, and Web of Science up to May 2025. Standardised mean difference (SMD) or mean difference (MD) were estimated in controlled and multi-intervention studies. Effect size indices were pooled using a random-effects model when at least three studies reported a specific outcome. Additionally, subgroup analyses were carried out based on AF type. Results Most of the studies used moderate intensity exercise (MIE). Across included studies, peak oxygen uptake (VO2 peak) (n = 5, N = 1,519), 6-min walk test (6MWT) (n = 5, N = 1,344), QoL (n = 9, N = 1,596), resting HR (n = 6, N = 490), AF burden (n = 5, N = 412), and AF symptoms (n = 4, N = 428) were reported. The results showed that aerobic exercise improves VO2 peak to a greater extent than usual care, regardless of AF type (MD+ = 4.24 [95%CI = 0.87; 7.45] ml/kg/min). Compared to usual care, aerobic exercise only diminished resting HR in non-permanent AF (MD+ = − 12.79 [95%CI = − 15.90: − 9.67] bpm). No differences were found for improving QoL and 6MWT (p > .050). The effect of exercise on AF burden and symptoms has been poorly studied. No pooled analyses were performed by including multi-intervention studies. The findings showed no influence of the aerobic intensity or modality. Conclusion Aerobic exercise improves VO2 peak in patients with permanent and non-permanent AF. MIE reduces resting HR in patients with permanent AF, while no differences were found in non-permanent AF. In contrast, the limited and heterogeneous RCT evidence available is insufficient to demonstrate superior improvements in the 6MWT or QoL compared to usual care. Further research is needed to determine the impact of CR on AF burden and symptoms, and to elucidate how exercise modality and intensity influence outcomes.